Immunomodulatory Effect of Colistin and its Protective Role in Rats with Methicillin-Resistant Staphylococcus aureus-induced Pneumonia - Niu, Hui; Yang, Tianli; Wang, Jin; Wang, Rui; Cai, Yun (Frontiers in Pharmacology, 2021)
Objectives: Colistin is the last resort of antimicrobials against multi-drug resistant Gram-negative pathogens. Previous studies in Caenorhabditis elegans and macrophages of rats have suggested that colistin possesses the immunomodulatory properties by acting p38/MAPK pathway. Here, we aimed to confirm the immunomodulatory role of colistin in animal models. Methods: Rat model of Methicillin-resistant Staphylococcus aureus (MRSA)-induced pneumonia was established. Plasma concentrations of proinflammatory cytokines, quantitative bacteriology, histology and immunohistochemistry of lungs were assessed to compare the immunomodulatory properties of colistin pre-administration. Results: The numbers of white blood cells and granulocytes were significantly increased in the 9 mg/kg colistin pre-administration group at 72 h after infection. Levels of TNF-α, IL-6 and IL-1β in plasma after colistin pre-administration were lower compared with the infected group without treatment. Colistin pre-treatment resulted in lower bacterial counts, a dramatic decrease of cytokines and improved histopathological injury in infected lung tissues compared with the untreated animals. However, p38/MAPK inhibitor SB203580 did not fully block the above-mentioned effects caused by colistin. Conclusions: Pre-administration of colistin could attenuate an excessive inflammatory reaction and protect the lungs from MRSA-associated damages. However, these effects could not be reversed by blocking the p38/MAPK pathway alone. Collectively, the mechanism underlying the immunoregulatory effects of colistin in mammals needs to be further explored.